UJI EFEKTIVITAS EKSTRAK BAWANG PUTIH (Allium sativum) TERHADAP PERTUMBUHAN BAKTERI DAN KUALITAS PADA IKAN PATIN (Pangasius sp) SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI SMA - Ria Rezki Oktafina; Irda Sayuti; Nusrsal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research was conducted to determine the effectiveness of garlic’s extract (Allium sativum) concentration on the bacterial growth and its quality on the Iridescent Shark (Pangasius sp) for the design of student worksheet done in June 2016. This research was carried out in two stages: the field research and the stage of designing student’s worksheet (LKS). The experimental research was conducted by using Complete Randomized Sampling (RAL) factorial, the first factor was garlics extract consisting of 4 treatments and the second factor was the storage duration consisting of 4 treatments and 3 replications so that there were 48 experimental units were obtained. Parameters observed include Total Plate Count (TPC) and organoleptic values that include appearance, odor and texture. The results showed that the concentration of garlic’s extract had an effect on the growth of the number of bacterial colonies. Where the growth of bacterial colony amounts occurs at treatment of BP3L1 (4.69 x 105). While the most preferred organoleptic test of panelists is the concentration of garlic’s extract (Allium sativum) 20% with the duration of storage time of six hours shows the best quality to the appearance (eyes, gills, surface mucus, meat), odor and texture. The results of the research are used as the design of student worksheet (LKS) on biology subject in high school.Keywords : Garlic, Iridescent Shark, Students Worksheet (LKS)